Illicit substance use among persons admitted to probation polyclinic of a regional mental hospital in the Eastern Anatolia, Turkey - Telo, Selda; Kaman, Dilara; Korkmaz, Sevda (Saudi Med J, 2016)
Objectives: To investigate the illicit substance use trends by gender and year in Eastern Turkey, Elazig. Methods: This is a retrospective study designed to assess the drug use prevalence in persons who admitted to the Probation Policlinic of Elazig Mental Health Hospital between January 2011 and December 2014 in Eastern Turkey, Elazig. Laboratory screening tests for drugs were studied using the cloned enzyme donor immunoassay technique in urine. Results: The study consisted of 10267 males (95.3%) and 510 females (4.7%), with a mean age of 30.42 +/- 10.83 years. Overall prevalence was 32.1% for cannabis, 3.8% for opiate, 0.35% for cocaine and 1.2% for polydrug usage. The prevalence of cannabis was significantly higher in males (32.7%, p=0.000). The prevalence of cannabis use was the lowest in the age group of 50-59 while it was significantly higher in the age groups of 20-29 and 30-39 (p=0.000). The prevalence of opiate use showed a significant difference among the years (p=0.000). There was a significant difference in the prevalence of cocaine use among the years (p=0.02). The prevalence of polysubstance use showed a significant difference among years (p=0.000). Conclusion: Cannabis was the most common illicit drug in the east of the Turkey. Further studies are required for comparing the results of various regions of the country and developing early interventions and treatment facilities.
Keywords: Drug-Abuse Patterns; Sociodemographic Characteristics; Risk-Factors; Use Disorder; Alcohol-Use; Prevalence; University; Trends